2021
DOI: 10.1186/s12984-021-00883-7
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Markov Model based stride segmentation on unsupervised free-living gait data in Parkinson’s disease patients

Abstract: Background To objectively assess a patient’s gait, a robust identification of stride borders is one of the first steps in inertial sensor-based mobile gait analysis pipelines. While many different methods for stride segmentation have been presented in the literature, an out-of-lab evaluation of respective algorithms on free-living gait is still missing. Method To address this issue, we present a comprehensive free-living evaluation dataset, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…Particularly in times of global pandemics, where the number of regular face-to-face visits is reduced (Roy et al, 2020), automatically extracted and shared parameters from wearables have the potential to support clinical decisions. Automatic evaluation methods of data from wearables in clinical gait and balance assessments (e.g., Karatsidis et al, 2017;Nguyen et al, 2019) but also in unrestricted activities of daily living (e.g., Roth et al, 2021) are constantly investigated. Machine learning techniques are the driving force behind this rapid growth of applications.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Particularly in times of global pandemics, where the number of regular face-to-face visits is reduced (Roy et al, 2020), automatically extracted and shared parameters from wearables have the potential to support clinical decisions. Automatic evaluation methods of data from wearables in clinical gait and balance assessments (e.g., Karatsidis et al, 2017;Nguyen et al, 2019) but also in unrestricted activities of daily living (e.g., Roth et al, 2021) are constantly investigated. Machine learning techniques are the driving force behind this rapid growth of applications.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, all strides in the dataset were labeled manually by gait experts independently based on the medial-lateral gyroscope signal of the instep sensor. The start and the end of each stride were marked based on the clearly visible minimum before the terminal contact (for more information about the labeling process see [ 31 ]). To ensure consistency, the manual labels were moved to the exact sample of the minima in a 50 ms window around the labeled point.…”
Section: Methodsmentioning
confidence: 99%
“…From the perspective of frequency signal decomposition, wavelet analysis provided insight into determining stride borders, and it is suggested that better performance could be achieved in the frequency domain than in the time domain [42][43][44][45]. Another kind of method employs Hidden Markov Models (HMM) [46][47][48], residual neural networks [29], etc. These methods could achieve better detection accuracy in stride segmentation or gait recognition assignments with the assurance that large-scale training data should be offered and massive computing resources supplied.…”
Section: Dataset Digital Biobankmentioning
confidence: 99%